(untitled) (Indian Journal of Experimental Biology (IJEB), 2026)
Dietary patterns characterised by excessive fat intake combined with inadequate micronutrient consumption are increasingly associated with metabolic disturbances, including obesity, insulin resistance, dyslipidemia, and organ-level dysfunction. Although Spirulina is recognised for its nutrient density and metabolic benefits, its efficacy under the compounded stress of a high-fat diet and concurrent micronutrient deficiency has not been systematically evaluated. Addressing this gap is important for developing nutritional strategies relevant to real-world dietary imbalances. This study investigated the ameliorative effects of Spirulina (Arthrospira) supplementation in Wistar rats fed either a high-fat (HF) diet or a micronutrient-deficient high-fat diet (HFD). Rats were initially maintained on Control (AIN-93G), HF, or HFD diets for 90 days. Thereafter, HF and HFD groups were subdivided to receive either the same diet or the respective diet enriched with 6.5% Spirulina biomass for an additional 60 days. HF and HFD feeding resulted in significant body-weight gain, elevated fasting glucose levels, impaired glucose tolerance, dyslipidemia, and marked histopathological alterations in the liver, heart, kidney, and testis. Spirulina supplementation moderated body-weight gain, restored fasting glucose and oral glucose tolerance to control levels, and normalised lipid parameters in both HF- and HFD-fed rats. Histological analyses further confirmed substantial recovery of tissue morphology following Spirulina intervention. In summary, Spirulina supplementation effectively mitigated metabolic and histological impairments induced by combined high-fat intake and micronutrient deficiency. These findings highlight Spirulina’s potential as a functional dietary adjunct for managing complex, diet-induced metabolic disorders.